Investigation of orbital characteristics of solar power for a LEO satelite - U Tun Tun Lwin (2008)
The main focus of this project is on Solar cells and its power characteristics. Since solar energy is always available in space (except when the satellite is in shadow) it is consider as a reliable power source for satellite communications.